Getting an Early Start in Understanding Perinatal Asphyxia Impact on the Cardiovascular System - Popescu, Mihaela Roxana; Panaitescu, Anca Maria; Pavel, Bogdan; Zagrean, Leon; Peltecu, Gheorghe; Zagrean, Ana-Maria (Frontiers in Pediatrics, 2020)
Perinatal asphyxia (PA) is a burdening pathology with high short-term mortality and severe long-term consequences. Its incidence, reaching as high as 10 cases per 1000 live births in the less developed countries, prompts the need for better awareness and prevention of cases at risk, together with management by easily applicable protocols. PA acts first and foremost on the nervous tissue, but also on the heart, by hypoxia and subsequent ischemia-reperfusion injury. Myocardial development at birth is still incomplete and cannot adequately respond to this aggression. Cardiac dysfunction, including low ventricular output, bradycardia, and pulmonary hypertension, complicates the already compromised circulatory status of the newborn with PA. Multiorgan and especially cardiovascular failure seem to play a crucial role in the secondary phase of hypoxic-ischemic encephalopathy (HIE) and its high mortality rate. Hypothermia is an acceptable solution for HIE, but there is a fragile equilibrium between therapeutic gain and cardiovascular instability. A profound understanding of the underlying mechanisms of the nervous and cardiovascular systems and a close collaboration between the bench and bedside specialists in these domains is compulsory. More resources need to be directed toward the prevention of PA and the consecutive decrease of cardiovascular dysfunction. Not much can be done in case of an unexpected acute event that produces PA, where recognition and prompt delivery are the key factors for a positive clinical result. However, the situation is different for high-risk pregnancies or circumstances that make the fetus more vulnerable to asphyxia. Improving the outcome in these cases is possible through careful monitoring, identifying the high-risk pregnancies, and the implementation of novel prenatal strategies. Also, apart from adequately supporting the heart through the acute episode, there is a need for protocols for long-term cardiovascular follow-up. This will increase our recognition of any lasting myocardial damage and will enhance our perspective on the real impact of PA. The goal of this article is to review data on the cardiovascular consequences of PA, in the context of an immature cardiovascular system, discuss the potential contribution of cardiovascular impairment on short and long-term outcomes, and propose further directions of research in this field.